Banking failures in Chile during the period of financial liberalisation - Araya Gómez, Ivan (1996)
It is argued that the banking crisis in Chile had its origin in the deterioration of key macroeconomic variables and that financial liberalisation played a secondary role. Proponents contend that no financial system can be expected to withstand a fall in output of nearly 15% in 1982 and they draw parallels here with the banking crisis of the 1930’s in the US. On the other side, it is argued that the ability of the financial system to withstand any macroeconomic shock have been shaped by the financial liberalisation which took place in the years before the collapse of the macroeconomy. Conduct derived from ownership concentration and “related portfolios”, sharp deregulation on interest rates, belief in an implicit bail-out provision, and the ineffective and inadequate prudential regulation led to pervasive banking structure and a pattern of behaviour marked by moral hazard. As a result, banks exhibited excessive risk taking with a deterioration of banks’ financial position. Only the prompt rescue by the Central Bank of leading financial institutions averted a massive loss of confidence and a bank run. This thesis examines the evolution of the Chilean financial system during the period of economic reforms and banking failures. Three specific questions are examined and evaluated empirically: How important was the adverse macroeconomic environment relative to the banking conduct and management which exhibited considerable moral hazard and adverse selection type of behavior in the banking failures in Chile? Secondly, in what ways might a more favourable general economic conditions and/or a more effective prudential regulation have helped to reduce the likelihood of bank failures? Finally, might some of the bank failures been anticipated years before the crisis by an early warning system? In order to answer these questions this thesis develops a logit model for cross-section and panel data with information from banks' balance sheets to estimate the probability of bank failure/problem for the period between 1979 and 1983.